AHSS auto structural metal stampings: Crucial role of lubricant - Baluch, Nazim Hussain; Nordin, Norani; Mohtar, Shahimi (Trans Tech Publications Inc., 2014)
To improve crash worthiness and fuel economy, the automotive industry is, increasingly, using Advanced High Strength Steel (AHSS).However, in recent years, stampers, particularly those serving the automotive industry, have begun to face new challenges related to the increased use of AHSS.Stamping AHSS can push the capability limits of some lubricants and often cause lubricant film break down and galling thereby increasing scrap rate and tool maintenance cost.This paper discusses the advantages of AHSS in auto metal stampings, highlights the new challenges faced by stampers, and delineates the exigency of draw lubricant in producing high quality auto stampings from AHSS.